Performance Parameters of a Closed Loop Thermosyphon - Nemec, Patrik; Malcho, Milan; Smitka, Martin; Matusov, Jozef (Communications - Scientific letters of the University of Zilina, 2012)
Devices composed of output electronic components produce waste heat that has to be dissipated to the environment. Heat removal by means of forced convection air cooling is quite often insufficient and new alternatives for cooling of output electronic components are being looked for. One option is the use of a closed loop thermosyphon. Theclosed loop thermosyphonis a simple and reliabledevice providing heat transfer. The paper deals with the cooling of an output electronic component by means of this device. It describes a design and construction of the device to provide heat removal from the electronic component, measurement of dependences of performance parameters on waste performance of the electronic component and their verification by means of a mathematic calculation based on physical phenomena of boiling, condensation and heat transfer.